Joy to the Work: How Does Software Team Formation Strategy Influence Job Satisfaction? - Cavalcante, Sergio Ricardo De Oliveira; Gadelha, Bruno; Oliveira, Edson; Steinmacher, Igor; Nakamura, Walter; Conte, Tayana (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS), 2022)
Background - The main assets of software organizations are their development teams. Several factors impact job satisfaction, such as salary, workload, and autonomy; still, the software team relationship could impact one’s job satisfaction. Objective - We aim to understand how software team formation strategy impacts job satisfaction. Method - We analyzed two software team formation strategies: (i) team members selected by a leader, and (ii) team members self-selection. We administered a survey to 66 employees of an R&D organization, comparing the team formation strategies. Results - Our results indicated that, in this context, the self-selection team formation strategy positively impacted job satisfaction and influenced good team cohesion and performance. Qualitative results showed that this formation strategy assembled teams with a good relationship among their members in which conflicts arose but were harmonically solved. Conclusion - This suggests that autonomy in the team formation stage would be good practice and could be more tested in the industry. These results may bring new evidence to practitioners about the benefits and drawbacks that self-selected teams may offer to the organization.